How does mainstream print media frame service delivery protests? The application of the protest paradigm and propaganda model in the South African case - Makanda, Mfundo Xolo (Centre for Film and Media Studies, 2023)
This thesis examines how the South African mainstream print media frame service delivery protests in the country. Studies in countries such as the United States (U.S.), Brazil and Canada show that media coverage of social movements conforms to the protest paradigm by depicting protesters as violent, destructive, unreasonable and a threat to the national economy. This thesis builds on existing literature on the protest paradigm, framing theory, agenda setting and the propaganda model (PM) to analyse mainstream print media coverage of service delivery protests in South Africa. The thesis examines the inclusion of the voices of protesters and women in the press, use of terminology, diversity of news content and media coverage of the underlying causes of the protests. This was done to determine how media coverage of protests in South Africa fits within the global debate on mainstream media coverage of social movements. A sample of 603 news articles from 10 different English-language mainstream newspapers were analysed longitudinally using a quantitative content analysis. The selected time, spanned over a six-year period starting on 15 January 2016 and ending on 12 August 2021. The findings showed that the media tends to marginalise protesters or groups that are challenging the status quo and thus the coverage of service delivery protests conforms to the protest paradigm. The mainstream press foregrounds episodic frames such as violence and destruction when reporting on these protests. The thesis concludes by illustrating that extensive coverage of violence associated with service delivery protests has a potential to escalate conflict instead of contributing to peaceful resolution of service delivery problems. Because of the power that the mainstream media holds in a society, the thesis proposes that the South African mainstream press could focus instead on alternatives to violence by emphasising positive action taken by both conflicting parties to solve service delivery problems.